Analisis Gaya Bahasa dalam Lirik Lagu Lenka Kripac Album Lenka - Miftahurrohman Miftahurrohman; Rr. Astri Indriana Octavita; Ira Miranti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The aims of this research are to describe figurative language and meaning of figurative language.The method of this research is descriptive qualitative method which analyzes figurative language.The result of this research is to find the figurative language song lyric Lenka Kripac. The results are repetisi with percentage 22,7%. Antisipasi, koreksio, sinisme, and koreksio are 2,3%.